Peningkatan Produktivitas Kelompok Tani Ikan Lele dengan Teknik Bioflok - Dwi Sudaryati; Sucahyo Heriningsih; Rusherlistyani Rusherlistyani (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2017)
Catfish is the type of fish that is mostly eaten and traded in traditional markets on the island of Java, not least in Central Java and Yogyakarta and surrounding areas. Catfish made into one type of side dish that comes from the most popular fish because in addition to the relatively affordable price of the general public is also easy to obtain. The purpose of this devotion program is to improve the productivity of catfish farming with biofloc techniques to increase yield and gain optimal benefits. To overcome the problem, the activities carried out are: (1) Counseling and mentoring of biofloc technique, (2) Counseling and guidance of catfish farming management and (3) Training and Guidance of bookkeeping of catfish farming business. The result of this dedication activity is shown by the increasing of partner motivation to run the catfish farming as an effort to improve the welfare of farmer group member. The training has succeeded in increasing the knowledge of farmer group members to increase production or harvest with biofloc technique, both disease prevention and maintenance and feeding and bookkeeping skills improvement.Keywords: Productivity, Cultivation of Catfish, Biofloc